RESEARCH EXPOSURE, ATTITUDE TOWARDS RESEARCH AND RESEARCH COMPETENCE OF THE SENIOR HIGH SCHOOL TEACHERS.: RESEARCH EXPOSURE, ATTITUDE TOWARDS RESEARCH AND RESEARCH COMPETENCE OF THE SENIOR HIGH SCHOOL TEACHERS. - Abinan, Anna Lizette (International Journal of Arts, Sciences and Education, 2021)
This study determined the research exposure, attitude towards research and research competence of the Senior High School teachers using the descriptive-correlational method of research. The study was conducted on the select Public Secondary Schools that offer senior high program in the whole District 1 of Cagayan. A total of 60 senior high school practical research teachers of the Department of Education were utilized as respondents. Findings revealed that most of the teachers handling practical research in the first district of Cagayan are predominantly young, female, mostly English in specialization, with average 6 years in the teaching service, currently on-going Masteral schooling (MA/MST.). majority has undergone Educational Research subject, and with local Research-related trainings. Moreso, Practical Research teachers in the Cagayan District 1 were found to have low exposure due to low number of research development, presentation and publication. Teachers have somewhat positive attitude towards research despite that they know the usefulness of research in their profession. Thus, the more useful the teachers think of research, the higher their level of positivity towards research. However, the higher their research difficulties, the higher is their level of research anxiety. Furthermore, the more experienced the teachers, the higher their level of competence. The more the teachers’ exposure in research, the higher their level of competence. The study provides input for recommendation towards the improvement of teachers’ research exposure, attitude and competence as practical research teachers.